Extraction of bioactive compounds from vine pruning residues by using ohmic heating and conventional heating techniques - Jesus, Meirielly Santos (2019)
Vine pruning residue (VPR), a waste from the wine production, has attracted the interest of chemical and food industries thanks to its great potential as a raw material to obtain bioactive compounds. Due to the high market price of these compounds, different technologies have been studied to improve the economic profitability of their obtaining process. Therefore, the objective of this work was to evaluate an emerging technology named ohmic heating (OH) against conventional heating (CH) to extract bioactive compounds from VPR with significant antioxidant and antimicrobial activities. Extractions were carried out using a 45% hydroalcoholic solution, a solid/liquid ratio of 1/40 (g VPR/mL solvent) at 80°C for 60 min and under constant stirring. Total phenolic compounds (TPC) of the extractes were evaluated and the bioactive compounds identified and quantified by HPLC. Moreover, the antioxidant potential of the recovered compounds was estimated by the methods of DPPH, FRAP and ABTS, and the antimicrobial activity through MIC assay was tested against five food pathogenic fungi. The OH extract showed higher TPC concentration (196.2 mg GAE/kg), being identified 12 polyphenolic compounds, twice the number of compounds found in the CH extract and revealing quercetin and apigenin (2867.8 and 1574.9 mg/kg, respectively) as the main compounds in OH extract. Moreover, OH extract showed higher antioxidant activity (432.7 mg FE/kg, 370.2, 207.4 mg TE/kg for FRAP, DPPH and ABTS, respectively) and better inhibitory effects against P. expansum, Alternaria sp., Phoma violacea, and C. cladosporioides (54.5, 45.4, 33.9, 59.9%, respectively) when 1000 g/mL of extract was used. These findings demonstrated the potential of VPR extracts as a probable source of bioactive compounds with relevant functional characteristics, as well as the efficiency of OH in the extraction of polyphenolic compounds from VPR, proposing a reduction in energy consumption and making the process more environmentally friendly.